China's Growth and Integration into the World Economy : Prospects and Challenges - Prasad, Eswar (Occasional Papers; Occasional Paper ;, 2004)
China's transformation into a dynamic private-sector-led economy and its integration into the world economy have been among the most dramatic global economic developments of recent decades. This paper provides an overview of some of the key aspects of recent developments in China's macroeconomy and economic structure. It also surveys the main policy challenges that will need to be addressed for China to maintain sustained high growth and continued global integration.